Platystele shanti, a petite novel jewel from Costa Rica - Karremans, Adam P. (Phytotaxa, 2024)
A new species of Platystele is described from the Juan Castro Blanco National Park area, around Ciudad Quesada in Costa Rica. The petite novelty is morphologically similar to P. propinqua (Ames) Garay, but with the leaves spathulate, the inflorescence pendent becoming two to three times longer than the leaf, and bearing up to 25 flowers per coflorescence. The yellow flowers suffused with reddish-purple are smaller, with the segments recurved, the sepals and petals are glandular papillose on the adaxial surface, and sepals have short, blunt tails. The new species grows as an epiphyte in primary and secondary forest at elevations ca. 1800–1900 m, and seems to be endemic to the windy slopes of the Platanar Volcano, where it is locally abundant.